Eruption cysts in the neonate - Ricci, Hérica Adad; Parisotto, Thaís Manzano; Giro, Elisa Maria Aparecida; De Souza Costa, Carlos Alberto; Hebling, Josimeri (MRE Press, 2008)
Disturbances of the dental development may result in anomalies, which may be apparent as soon as the child is born. Eruption cysts are rarely observed in neonates considering that at this stage of the child's life teeth eruption is uncommon. Thus, the aim of this report is to describe a case of eruption cysts in a neonate. A male neonate was brought to the emergency service with the chief complaint of an elevated area on the anterior region of the inferior alveolar ridge. The lesion was clinically characterized as a compressive and floating swelling. Through a radiographic exam two mandibular primary incisors could be seen superficially located. Due to the patient's age and the initial diagnosis of eruption cysts the conduct adopted was clinical surveillance. Forty-five days after the first visit the lesions had significantly decreased in size, and completely disappeared after 4 months. At that age, both mandibular central incisors were already in the oral cavity exhibiting small hypoplastic areas in the incisal edges. The clinical and radiographic follow-up of eruption cysts in neonates appears to be an adequate conduct without differing from that recommended for older children.
Keywords: Case report; Eruption cyst; Neonate